Easy way to solve two-loop vertex integrals - Suzuki, Alfredo T.; Schmidt, Alexandre G. M. (American Physical Society (APS), 1998)
We consider tour two-loop three-point vertex diagrams with arbitrary exponents of propagators and dimension, three of them with two legs on-shell and one with all legs off-shell. As far as we know there is no similar calculation in the literature, and our original results are neatly expressed in terms of products of gamma functions.